The role of vitamin K in osteoarthritis - Pereira, Carla Margarida da Silva (2016)
Osteoarthritis (OA) is the most frequent chronic rheumatic disease, affecting approximately 15% of the population, with a higher prevalence among the elderly; occurring in synovial joints such as the hips, knees and the ankle. This condition develops when the joint organ homeostasis is affected, causing abnormal remodeling of the articular tissues, leading to degradation of the cartilage, thickening of the subchondral bone, formation of osteophytes and variable degrees of inflammation. The burden of OA clinically characterized by chronic pain and significant disability is high, and only few nonpharmacologic and pharmacologic treatment options are available, mostly focused on providing symptomatic relief and showing limited efficacy and several side effects. The research on this disease in need for novel therapeutic alternatives has increased and lately is becoming fully recognized that joint’s calcification and the crosstalk with inflammation should be considered as an OA therapeutic target. In this context, vitamin K has been recognized as playing multifunctional roles that may modulate the pathogenesis of the disease. Vitamin K acts as an essential coenzyme in the post-translational modification of specific glutamic acid residues (Glu) into γ-carboxyglutamic acid residues (Gla) in target proteins, known as vitamin K-dependent proteins (VKDPs), to make them biologically active. Mineral-related Gla proteins, have been proposed as regulators of cell differentiation and inhibitors of mineralization in articular systems, so impairment in their γ-carboxylation status should have an impact in joint’s health, showing a plausible rationale for the connection of vitamin K through the OA stages. This old vitamin is now presented in a new perspective, with emerged value in human’s health, crucial in the prevention of pathological calcification and an important protective tool against inflammation and oxidative stress; revealing a promising potential as a prophylactic and therapeutic agent in OA.